Impact of education and training on LGBT-specific health issues for healthcare students and professionals: a systematic review of comparative studies - Kate Jolly; Ameeta Retzer; Sarah Damery; Nicola Kay Gale; Adekemi Oluwayemisi Sekoni; Ifeoma Okafor; Bibiane Manga-Atangana; Rachel Posaner (BMJ Open)
Objectives Training/education is increasingly used to improve healthcare professionals’ knowledge, attitudes and clinical skills about lesbian, gay, bisexual and transgender (LGBT) health, but few reviews have assessed their effectiveness. This review describes the impact of training about LGBT healthcare for healthcare professionals on participants’ knowledge, attitudes and clinical practice.Design Systematic review of intervention studies with contemporaneous comparators.Data sources Medline, CINAHL (Cumulated Index in Nursing and Alllied Health Literature), PsycINFO, Social Sciences Citation Index, Education Resources Information Center, Cochrane Library, University of York CRD, PROSPERO and Ethos e-thesis database were searched from 15/12/2015 to 29/11/2023 to update a review published in 2017.Eligibility criteria Interventional studies of training/education for healthcare professionals or students about LGBT-specific health issues, compared with standard or no training/education. Outcomes were changes in participants’ knowledge, attitudes or clinical practice regarding LGBT health.Data extraction and synthesis Reviewer pairs independently screened titles/abstracts and full texts. Data were extracted by one reviewer and checked by a second (population, training content, development, delivery, duration/intensity and outcomes). The National Institutes of Health tool for controlled intervention studies assessed study quality. Synthesis was descriptive.Results 11 734 citations were screened, and 10 studies were included. 8/10 were published since 2019. Study quality was poor (8/10) or fair (2/10), and all were conducted in high-income countries. Four focused on transgender care. All studies used multi-component approaches, with topics covering terminology, lived experience, LGBT-specific health, sexuality and sexual history taking. Training duration ranged from 40 min to 50+ hours. Five studies included LGBT individuals in training development and/or delivery. 7/7 studies assessing attitudes, 2/4 studies assessing knowledge and 4/6 studies assessing skills/practice (actual or intended) reported statistically significant improvements.Conclusions Multi-component healthcare professional training on LGBT health can significantly improve participants’ knowledge, attitudes and skills. However, there was substantial heterogeneity in training content, delivery and duration, and most studies were of poor quality.PROSPERO registration number CRD42023414431 (26/06/2023).